Coupled Inductor-Based Single-Switch Quadratic High Step-Up DC-DC Converters With Reduced Voltage Stress on Switch - Habibi, Saeed; Rahimi, Ramin; Ferdowsi, Mehdi; Shamsi, Pourya (IEEE journal of emerging and selected topics in industrial electronics (Print), 2023)
In this article, two single-switch quadratic boost converters based on a three-winding coupled inductor (CI) are proposed. These converters provide a high voltage gain in a low duty cycle, reduced voltage stress on the power switch, continuous input current with a low di/dt, higher design flexibility, and limited current falling rate on the voltage multiplier diodes to minimize the reverse recovery loss. Moreover, the first proposed converter has two capacitors in the output reducing the need for a bulky output capacitor, while the second proposed converter has higher utilization of the CI and is able to provide a higher voltage gain. The operation principle and theoretical analysis, such as voltage stress, current stress, effect of leakage inductances on the voltage gain, and design considerations are presented in this article. Furthermore, the superiority of the proposed converters over the competitive high step-up quadratic converters are justified through a comparison study. Finally, a 300-W, 30- to 400-V laboratory experimental setup is implemented to validate the theoretical analysis.